Selections from Leaves of grass - Whitman, Walt 1819-1892 (Avenel Books, 1961)
As energetic and diverse as the American life it describes, Walt Whitman's Leaves of Grass has been loved by generations for its celebration of a brash young nation and one man's exuberant spirit. First published at the author's expense in 1955, this collection of poems was revised and enlarged throughout Whitman's lifetime, and is presented here in the final or "Deathbed edition" of 1892.